L’invenzione giuridica e letteraria di una plurale storia costituzionale e sociale d’Italia. A proposito di un libro recente - Allegri, Giuseppe (Studi Politici, 2022)
This note presents a collective volume reflecting on Italian constitutional history through literature. The essays interrogate the relationships between literary imaginaries and constituent and constitutional tensions with a historical, literary, and legal comparison that fits into the studies of law and literature.